Study on the use of redox electrolytes in supercapacitors - Akinwolemiwa, Bamidele (2019)
Electric double layer (EDL) capacitors (a.k.a. supercapacitors) which are generally characterised by high power and long cycle lives, exploits the electrostatic interaction between electrons and ions within the porous matrix of carbonaceous materials with high specific surface area ranging from 500.00 to over 2,000.00 cm2/g.